Efecto de fitomejoradores biológicos en cacao nacional - Bermeo Macas, Carlos Ivan (2012)
In the Granja Santa Ines of the Technical University of Machala, during the season of March to September 2011, investigated the effects it produces the biological plant breeders in the organic system in national cocoa in a plantation with 30 years of age that was abandoned. The objectives of this study were the following: 1. Determine the efficiency of biological plant breeders in the performance of the national cocoa. 2. Determine the extent of absorption of nutrients from the plant. The treatments investigated were: T1 Ecoflora (800 g/ha/year), T2 Ecofungi (3 kg/ha/year), T3 Concat G-3 (200 g/ha/year), T4 Radiplus (4 L. /ha/year), T5 Microplus (1 kg/ha/year), T6 Control (agricultor comun). Which were allocated to plots or experimental units distributed according to the schema of a design in a random blocks with 6 treatments and 4 repetitions, totaling 24 experimental units or parcels. Breeders biological increment the soil into the neck of he plant in the above dose every 4 months for each treatment through the Atomisation. During the development of the research was presented mild attacks of monilia (Moniliophthora roreri.) and broom (Crinipellis perniciosa) which were controlled with cultural work. The results and statistical analysis showed statistical significance for the 6 variables evaluated, an increase in the root mass, increase in flowering of floral bearings, absorption of nutrients, weight, length and diameter of the cobs and yield per hectare. Nutrients P, Ca, Mg and S were not absorbed as required by the plant, the best treatment significantly expressed in the variables quick links was the Ecofungi which is composed of an association of ecto and morph.